Liliom Based on a Play by Ferenc Molnár - Molnár, Ferenc (Frank Borzage - Volume Two, 2009)
Julie (Hobart) is a somewhat shy girl who loves arrogant ladies man Liliom (Farrell) from afar. They finally meet one night at the carnival where Liliom works as a barker at the carousel. When he flirts with Julie, his boss, Madame Muskat (Taylor), who has a thing for Liliom herself, fires him. Liliom and Julie marry, but Liliom spends his days laying about without a job. Julie loves him, and he loves her, despite the fact that he doesn’t treat her very well. When he finds out she’s pregnant, he decides to join up with a friend in a robbery. But, as usual, things go very wrong ... [obscureclassics.wordpress.com]